RESEARCH ON THE ENVIRONMENTAL QUALITY IN TELEORMAN RIVER BASED ON THE MACROZOOBENTHIC ANALYSIS - Alina - Mihaela Truţă (Current Trends in Natural Sciences, 2018)
The main purpose of the study was to determine the quality of Teleorman River. The present paper was based on the bibliographic material as well as the field research carried out during 2016-2017. The research objectives were the following: identification of the structure of benthic biocenoses in the monitoring points; establishing saprobity indices for each species identified and incorporation of the monitoring sections into the appropriate saprobity class; determining the quality of Teleormana River according to the Water Framework Directive 2000/60/EU, especially through analysis of Ephemeroptera fauna. The main benthic invertebrate groups in the Teleorman River were: Ephemeroptera, Plecoptera, Chironomidae, Trichoptera, and Gammaridae. In the structure of benthic zoocenosis, we have identified 14 species of Ephemeroptera, belonging to 6 families from 8 genera. Buzoiesti and Vulpesti recorded a high quality ecological status, while Magura station had a good ecological status.